O livro internacional para o ensino de língua inglesa à luz do interacionismo sociodiscursivo: Wider World - um estudo de caso - Amarante, Priscila de Queiroz (2023)
The English language textbook is one of the primary resources teachers used to teach English in language courses since national and international publishers offer a vast quantity and variety of textbooks. Considering this context, this research, inserted in applied linguistics area and from a qualitative nature, aims to analyze the book Wider World 1, a didactic material designed to adolescent audiences, and to assess the contributions of this material to the language learners’ development skills, considering the theoretical framework of Sociodiscursive Interactionism (ISD). In addition, three specific goals have been established: 1) analyze the teacher's book 1 (Teacher's Book – TB) of the Wider World collection (Pearson Education, 2019) to comprehend the theoretical concepts that underlie the proposal and dynamics of the collection as a whole; 2) analyze the student’s textbook 1 (Students’ Book 1 - SB) to understand the structure of the book and identify recurring patterns within the units, which will help define the analysis categories, presenting an overview of the material; 3) investigate the presence of written textual genres from SB 1 (Pearson Education, 2019) as tools for reading and writing activities to demonstrate whether and how these activities have the potential to promote the development and expansion of the learner's language capabilities. In order to support the analysis, a bibliographic study was conducted in which the primary theoretical framework referring to the ISD, language capabilities, and textual genres was constructed from Bronckart’s Genevan chain (1999; 2006; 2008) Schneuwly and Dolz (2004), Dolz, Pasquier, and Bronckart (2017), Machado and Bronckart (2009), Stutz and Cristóvão (2011), Magalhães and Criatovão (2018), among others. The results of this investigation indicate that the analyzed material is theoretically based on the communicative approach (CA) for developing linguistic skills. However, despite these intentions, the material shows weaknesses and can be characterized as following a more traditional concept that prioritizes grammatical and vocabulary learning. Concerning the development of language skills, the book does not present significant potential for fostering these skills through a CA. It is mainly due to the lack of authentic evidence in the genres within the units. Besides, reading and writing activities do not interact with each other. Another issue is that the proposals for activities related to the units' text genres do not focus on meaning; and almost the time, they do not seek reading comprehension and written production. Instead, the texts support the theme's development and the development of linguistic elements most of the time. Such aspects can hinder the learner's engagement with their language learning process and do not enhance the development of language skills.